2021
DOI: 10.1177/00469580211060779
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Pharmaceutical Data Associated With Hospital Readmission in Persons With Diabetic Foot Ulcers

Abstract: Purpose: Diabetic foot ulcers (DFUs) are a leading cause of lower extremity amputations among persons with diabetes (PWD) and a common cause of hospitalizations. This study identified demographic characteristics, lab values, and comorbidities associated with 30-day and 90-day hospital readmission in persons with DFU. Methods: A retrospective chart review at our institution examined 397 patients with type 2 diabetes admitted with DFU between January 2014 and December 2018. Variables were analyzed using descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies revealed that the median length of hospital stay of patients with DFU was 26–31 days, 22,23 which is consistent with our results. Demographic characteristics (including sex and age), laboratory results (including CRP and HbA1c), and underlying diseases (including PAOD and ESRD) were not associated with 30-day readmission in patients with DFU 24 . The rate of amputation in diabetic patients varied overtime and across countries.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies revealed that the median length of hospital stay of patients with DFU was 26–31 days, 22,23 which is consistent with our results. Demographic characteristics (including sex and age), laboratory results (including CRP and HbA1c), and underlying diseases (including PAOD and ESRD) were not associated with 30-day readmission in patients with DFU 24 . The rate of amputation in diabetic patients varied overtime and across countries.…”
Section: Discussionmentioning
confidence: 90%
“…Demographic characteristics (including sex and age), laboratory results (including CRP and HbA1c), and underlying diseases (including PAOD and ESRD) were not associated with 30-day readmission in patients with DFU. 24 The rate of amputation in diabetic patients varied overtime and across countries. Previous studies reported that 20%-50% of patients with DFUs eventually underwent amputation.…”
Section: Discussionmentioning
confidence: 99%